Prototype Environment for integrating and sharing Farm Things and associated data - Nikander, Jussi; Linkolehto, Raimo; Jäger, Markus; Pesonen, Liisa; Ronkainen, Ari; Suokannas, Antti (Cambridge University Press, 2017)
Farm equipment, including sensors and mobile machinery, create increasing amounts of data, and data can also be gained from third-party services. In order to be able to fully take advantage of this a farmer needs to be able to gather, store, process, and share the data as needed. In this work we describe a prototype for open environment that can gather, combine, store, select, and share data from arbitrary sources and with external partners, as well as use the data in decision making and provide it as input for various services. The environment is built using the Service Oriented Architecture paradigm and is therefore not tied to any specific operating system or software framework. We have tested the environment on the farm scale in Finland. The system was found suitable to improve the work in all tested tasks.
Keywords: farm data; internet of things; service oriented architecture; farm management; internet; precision agriculture